2014
DOI: 10.1152/ajpendo.00619.2013
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 isoform-specific deletion reveals a role for diet-induced insulin resistance

Abstract: However, the in vivo function of the ROCK1 isoform in adipose tissue has not been addressed. To determine the specific role of the adipose ROCK1 isoform in the development of insulin resistance and obesity, mice lacking ROCK1 in adipose tissue globally or selectively were studied. Here, we show that insulin's ability to activate IRS-1/PI3K/ Akt signaling was greatly enhanced in adipose tissue of ROCK1 Ϫ/Ϫ mice compared with wild-type mice. These effects resulted from the inhibitory effect of ROCK1 on insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 49 publications
1
70
1
1
Order By: Relevance
“…This is in contrast to the results of previous studies of ROCK2 regulation of insulin signaling in cultured 3T3-L1 adipocytes and L6 myoblasts, in which ROCK2 siRNA altered the phosphorylation of IRS and/or its downstream target Akt (10). This difference may be an indication of the complex tissue-and cell-specific regulation of insulin signaling by ROCK isoforms that has been noted in previous studies (5,10,23,30). Alternatively, it is possible that the residual ROCK2 protein levels in the ROCK2 ϩ/Ϫ mice were sufficient to maintain normal IRS phosphorylation, whereas levels achieved by ROCK2 siRNA in the cells were not.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the results of previous studies of ROCK2 regulation of insulin signaling in cultured 3T3-L1 adipocytes and L6 myoblasts, in which ROCK2 siRNA altered the phosphorylation of IRS and/or its downstream target Akt (10). This difference may be an indication of the complex tissue-and cell-specific regulation of insulin signaling by ROCK isoforms that has been noted in previous studies (5,10,23,30). Alternatively, it is possible that the residual ROCK2 protein levels in the ROCK2 ϩ/Ϫ mice were sufficient to maintain normal IRS phosphorylation, whereas levels achieved by ROCK2 siRNA in the cells were not.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, ROCK1 is required for normal insulin sensitivity in mice, since its deletion was associated with reduced tyrosine phosphorylation of IRS and impaired glucose transport in skeletal muscle (21). However, recently, ROCK1 was also shown to negatively regulate insulin signaling in adipose tissue (23). On the other hand, ROCK2 has been implicated in reduced insulin signaling in cultured mouse embryonic fibroblasts (30) and vascular cells (5) by promoting insulin-induced phosphorylation of serine residues in IRS-1.…”
mentioning
confidence: 99%
“…Thus, in adipose tissue, ROCK1 negatively controls insulin action in vivo. However, loss of adipose ROCK1 leads to increased insulin receptor signaling, with a minor effect on whole-body metabolism and glucose homeostasis (Lee et al, 2014b). These data also collectively confirm the complex and tissue-or cellspecific role of ROCKs in glucose metabolism and insulin signaling.…”
Section: Glucose Metabolismsupporting
confidence: 66%
“…Despite their insulin resistance, Rock1 2/2 mice display an increase in proximal insulin signaling in adipose tissue, and adipose tissue-selective deletion of Rock1 slightly ameliorates insulin sensitivity in the high-fat diet model of insulin resistance (Lee et al, 2014b). Thus, in adipose tissue, ROCK1 negatively controls insulin action in vivo.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…109 Interestingly, it was recently shown that adipose specific ROCK1 deletion in mice resulted in enhanced insulin signaling, suggesting that ROCK1 deletion had a protective effect against insulin resistance in this tissue. 133 These data suggests that there are tissue or cell type specific roles for ROCK1 in regulating glucose metabolism. Further genetic studies are required to determine the contribution of the ROCK2 isoform in insulin signaling and glucose homeostasis.…”
Section: Therapeutic Implications: Insights From Genetically Modifiedmentioning
confidence: 93%